Glycerol as a Binder Additive for Low-Resistance Graphite Anodes in Lithium-Ion Batteries. Issue 4 (1st April 2022) - Park, Kiho; Kim, Sungchan; Kim, Jaemin; Seo, Gyuwon; Baek, Minsung; Cho, Yunshik; Lee, Jungmin; Choi, Jang Wook
Abstract : Lithium-ion batteries (LIBs) have matured as a technology and serve as power sources in a wide range of applications. Nonetheless, emerging applications, represented by electric vehicles, have been imposing ever-challenging criteria with regard to the key electrochemical properties. Low-resistance anodes are highly desired for high-power and supercharging capabilities of LIBs, and these properties are collectively determined by the electrolyte composition and electrode binder. Here, we report the use of glycerol as an additive to the conventional styrene-butadiene rubber/carboxymethyl cellulose (SBR/CMC) binder for graphite anodes with the aim of lowering the interfacial resistance and thus improving the operating capability at high C-rates. Glycerol, as a plasticizer, increases the interchain free volume in the binder network and also promotes the dissociation of lithium salt owing to its high dielectric constant, both of which jointly facilitate lithium ion diffusion at the anode interface. As a result, the addition of a small amount (0.18 wt% of the entire electrode) of glycerol enhances the high-rate capability (i.e., >1 C). This study highlights the usefulness of small molecules as binder additives for improving the key performance parameters of LIBs without sacrificing other critical properties.